Predicting speech perception outcomes following cochlear implantation in adults with unilateral deafness or highly asymmetric hearing loss. (1st April 2016) - Kitterick, Pádraig T.; Lucas, Laura
Abstract : Objective: Unilateral deafness and highly asymmetric hearing loss can impair listening abilities in everyday situations, create substantial audiological handicap, and reduce overall quality of life. Preliminary evidence suggests that cochlear implantation may be effective in reversing some of these detrimental effects. Patient-level data from existing studies were re-analysed to explore potential factors that may be predictive of improved speech perception scores following implantation. Methods: Logistic regression modelling examined whether improved speech perception following implantation under various listening conditions was related to the duration of deafness of the severe-to-profoundly deaf ear and/or the level of hearing in the better ear. Results: Patients with a shorter duration of deafness were more likely to improve in listening conditions that created a less favourable SNR at the implanted ear than the non-implanted ear. Those with more residual hearing in the better ear were more likely to improve in the listening condition that created a less favourable SNR at that ear. Discussion: The analysis suggests that characteristics of both ears may be relevant when seeking to identify those candidates who are likely to obtain benefit to speech perception following cochlear implantation.